In vivo amyloid staging in individuals with subjective cognitive decline in DELCODE Study. (December 2021) - Levin, Fedor; Grothe, Michel J.; Dyrba, Martin; Boecker, Henning; Daamen, Marcel; Lange, Catharina; Buerger, Katharina; Heneka, Michael T.; Laske, Christoph; Peters, Oliver; Priller, Josef; Ramirez, Alfredo; et al.
Abstract: Background: In previous research, a data‐driven in vivo staging model of amyloid accumulation was established based on regional frequencies of amyloid positivity in 18 F‐florbetapir‐PET scans of cognitively normal older adults. The model was subsequently validated in an independent cohort of participants with subjective memory complaints. In the current study we aim to apply this staging approach in an independent sample of individuals with subjective cognitive decline (SCD) in the multicenter DZNE ‐ Longitudinal Cognitive Impairment and Dementia Study (DELCODE). Method: PET scans with 18 F‐florbetaben were obtained in a group of 63 SCD participants (mean age = 71.84y, range: 60.83‐83y; 35% female) from the DELCODE cohort. Participants also underwent MRI acquisition, clinical and neuropsychological assessments. CSF biomarkers and APOE genotypes were assessed for subsets of participants. In the future analysis we will classify participants into amyloid accumulation stages based on regional amyloid positivity as assessed in PET images. Result: Among participants with available CSF assessments, 38% had abnormal CSF Aβ42/Aβ40 ratio values indicating amyloid positivity. Frequency of APOE4 allele carriers of 39% was suggestive of APOE4 enrichment. Conclusion: SCD participants studied within the DELCODE represent a group at an increased risk for preclinical AD. Consistent with that, the current SCD subsample with available 18 F‐florbetaben‐PET scans demonstrated heightened rates of abnormal CSF amyloid‐β biomarkers and APOE4 prevalence. Investigation of regional amyloid accumulation in this sample would help assess the validity of the previous in vivo amyloid staging model in preclinical AD, as well as further characterize SCD. In the future analysis we will apply the previously established amyloid staging approach. We will additionally evaluate the hypothesized links between amyloid accumulation stages, cognitive performance, CSF biomarkers and prevalence of APOE genotypes.